Promoting and Hindering Health and Well-Being in Firefighter Discourse. (December 2020) - Jacobsson, Ann; Backteman Erlanson, Susann; Brulin, Christine; Egan Sjolander, Annika
The aim of this critical discourse analysis is to identify and discuss dominant and recurrent themes in firefighter discourse that promote and hinder firefighters' health and well-being. Using critical discourse analysis, the focus is directed toward routine work culture at the station, as well as how firefighters deal with extraordinary events. The empirical material was collected from rescue services in Sweden representing different geographical areas. In total, 28 firefighters participated in focus group discussions or individual interviews. We identified dominant themes in the discourse that promoted firefighters' health and well-being. We also identified recurrent themes that may serve as hindrances to health and well-being. We note that themes in the latter category also relate to changes in the profession and work culture, expressing external pressures on the rescue service. One reason for resistance toward change might be the health benefits that the current order of firefighter discourse brings.